2016
DOI: 10.1186/s12913-016-1710-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based generalisations in school nurses’ appraisals of and interventions addressing students’ mental health

Abstract: BackgroundThere has been an increase of reports describing mental health problems in adolescents, especially girls. School nurses play an important role in supporting young people with health problems. Few studies have considered how the nurses’ gender norms may influence their discussions.MethodsTo investigate this issue, semi-structured interviews focusing on school nurses’ work with students who have mental health problems were conducted. Transcripts of interviews with Swedish school nurses (n = 15) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…A previous pilot study, part of a wider interventional project called Help overcoming pain early (HOPE), confirmed previous findings that school nurses can play important roles in countering students' mental health and recurrent pain problems (Rosvall & Nilsson, 2016a, 2016b for similar results see Odenbring, 2019). It also highlighted the importance of nurses collaborating with other school staff, including all teachers (especially those involved in physical education and special needs specialists) and heads.…”
Section: Introductionsupporting
confidence: 68%
“…A previous pilot study, part of a wider interventional project called Help overcoming pain early (HOPE), confirmed previous findings that school nurses can play important roles in countering students' mental health and recurrent pain problems (Rosvall & Nilsson, 2016a, 2016b for similar results see Odenbring, 2019). It also highlighted the importance of nurses collaborating with other school staff, including all teachers (especially those involved in physical education and special needs specialists) and heads.…”
Section: Introductionsupporting
confidence: 68%
“…[9] They are more vulnerable to stress than adolescent boys[10] because of the inherent physiological changes, their social upbringing,[11] and a feeling of greater pressure to achieve good academic grades at an early age. [12] Although anxiety and depression affect boys and girls almost similarly, the adolescent girls are much more vulnerable. Recently, subjective stress related mental health complaints such as pain, sleeping problems, and anxiety have increased among older adolescents, especially girls.…”
Section: Introductionmentioning
confidence: 99%
“…One of the initial studies in the development of the HOPE programme reported stereotyped values arising from school nurses’ views of gender [47]. These stereotypes can hinder dialogue with adolescents, which renders an increased awareness of gender perspectives necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The HOPE programme contains a lecture and a film about gender perspectives for about 35 min. Besides, school nurses read an article that compares the HOPE and DISA programmes [47]. DISA has been criticised for reinforcing the stereotypical notions that girls are depressive and have low self-esteem [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation